Evaluasi Tingkat Kepatuhan Penggunaan Obat Antiepilepsi (OAE) terhadap Fungsi Kognitif Anak - Anida, Rizki Putri Ayu Dwi; Kresnapati, I Nyoman Bagus Aji; Pratiwi, Baiq Yulia Hasni (Biocity Journal of Pharmacy Bioscience and Clinical Community, 2024)
Epilepsy is a chronic brain disorder with various causes characterized by recurrent attacks. Epilepsy can affect all ages, including children, which affects around 40%-50%. Epilepsy can have an impact on memory disorders, either caused by symptoms of epilepsy itself, antiepileptic drugs (AEDs), psychosocial factors, or comorbidities. Patients with epilepsy are generally advised to consume AEDs for more than 3 months. This antiepileptic treatment takes a long time, so it is very susceptible to causing patient non-compliance in taking AEDs. Therefore, this study aims to determine the level of compliance of pediatric epilepsy patients and whether there is a relationship between compliance and the cognitive function of pediatric patients. In this study, 54 respondents were used from the Mataram City Hospital polyclinic. Compliance was measured using the Morisky Medication Adherence Scale 8 item (MMAS-8) questionnaire and cognitive function measure using the Indonesian version of the Montreal Cognitive Assessment (MoCA-Ina). The result based on the MMAS-8 shows that  7.4% of respondents had high compliance, 61.1% had moderate compliance, and 31.5% had low compliance. Data analysis used the Chi-Square test with α = 0.01 and obtained a significance value (p-value = 0.329). Based on these results, it can be concluded that the level of compliance is moderate, and there is no relationship between compliance and cognitive function.